Analysis of Spiritual Renewal in Christian Life According to 1 Peter 2:1-4 - Marlianti Hasibuan; Djone Georges Nicolas; Wernye Rahmat Wati Lawolo; Arthur fredryk Sahetapy; Yulianti Fransiska (PT FORMOSA CENDEKIA GLOBAL, 2022)
This writing aims to describe the spiritual renewal of Christian life based on 1 Peter 2:1-4. In this paper using exegesis and qualitative descriptive approach, by collecting data through the Bible, other literature books such as journals, interviews and documents related to the object of research. In Christian life, spiritual renewal is a priority for church leaders. However, spiritual renewal is certainly inseparable from various challenges and problems. Allegedly at this time the lives of believers still prioritize deception and have a hypocritical nature and the habit of slandering others. As a result, spiritual renewal in the lives of believers occurs because they live in holiness, become healthy spiritual babies and live relying on God. In conclusion, to increase spiritual renewal, God's people must be like babies who have just come into the world, namely thirsty for milk that has not sinned and is spiritual, because believers have received salvation